2014
DOI: 10.1186/1475-2875-13-147
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of haemozoin-based diagnosis of Plasmodium falciparum using dark-field microscopy

Abstract: BackgroundThe haemozoin crystal continues to be investigated extensively for its potential as a biomarker for malaria diagnostics. In order for haemozoin to be a valuable biomarker, it must be present in detectable quantities in the peripheral blood and distinguishable from false positives. Here, dark-field microscopy coupled with sophisticated image processing algorithms is used to characterize the abundance of detectable haemozoin within infected erythrocytes from field samples in order to determine the wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…Moreover, spontaneous Raman spectroscopy combined with other approaches such as confocal microscopy 24 or optical tweezers 25 have shown great promise for malaria diagnosis 26 . However, the amount of hemozoin produced in the early ring stages normally seen in peripheral blood is very small and parasites younger than 6 hours post invasion do not contain hemozoin detectable by the dark-field microscopy method 27 , even dark-field microscopy has improved sensitivity as compared to traditional light microscopy 28 . Therefore, the enhancement of Raman signals is crucial for the detection of hemozoin in early ring stages so as to provide the sensitivity needed for diagnosis 17 .…”
mentioning
confidence: 99%
“…Moreover, spontaneous Raman spectroscopy combined with other approaches such as confocal microscopy 24 or optical tweezers 25 have shown great promise for malaria diagnosis 26 . However, the amount of hemozoin produced in the early ring stages normally seen in peripheral blood is very small and parasites younger than 6 hours post invasion do not contain hemozoin detectable by the dark-field microscopy method 27 , even dark-field microscopy has improved sensitivity as compared to traditional light microscopy 28 . Therefore, the enhancement of Raman signals is crucial for the detection of hemozoin in early ring stages so as to provide the sensitivity needed for diagnosis 17 .…”
mentioning
confidence: 99%
“…Due to its birefringence and excellent light scattering hemozoin has been suggested as a promising target for non-invasive fast detection of malaria in unstained blood smears by cross-polarizing (xP) microscopy 16 and FSDF 17 18 . FSDF gives relatively low contrast, with a signal-to-noise ratio (SNR=maximal hemozoin pixel value/maximal empty erythrocyte pixel value) around 1.5–3, which does not allow clear identification of infected cells in crowded blood smears 4 19 . xP microscopy is more sensitive than FSDF 20 , though polarizing filters are relatively expensive.…”
Section: Resultsmentioning
confidence: 99%
“…xP microscopy is more sensitive than FSDF 20 , though polarizing filters are relatively expensive. An alternative advanced BSDF method was reported to increase SNR up to 50 4 19 , which opens up the possibility of automatic detection of the infection. This method combines xP imaging with a sophisticated DFSR system with sample illumination angle varying between 15–45°.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hz is higher in gametocytes than in most asexual forms of P. falciparum, providing aid in identification (6). Although Hz levels in early P. falciparum ring-forms are below the detection thresholds of both dark-field microscopy (49) and flow cytometry (31) when analyzing native samples, it may be detected in bulk in blood after rigorous lysis of the sample (50). Even though we have shown that free synthetic Hz can be easily detected by flow cytometry (Fig.…”
Section: Hemozoin Is a Useful And Simple Parameter To Measurementioning
confidence: 99%